2021
DOI: 10.1177/09722629211038069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Information and Argument Concreteness on Purchase Intention of Consumers Towards Online Hotel Booking

Abstract: Online consumer reviews impact the traveller’s decision to book hotel online. The study examines the role of visual information and argument concreteness on the credibility of reviews and consequently on purchase intention. The study examines the effect of trust and perceived risk as mediators on the relationship of review credibility and purchase intention. An online survey was conducted on 310 travellers above 18 years. The data was analysed using PLS-SEM. Travellers believed visual information and argument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Zarifah Dhabitah Mahat and Hafiz Hanafiah (2020) found a partial mediation effect of trust in the relationship between travelers' information adoption and behavioral intentions. Further, trust was found to mediate the relationship between review credibility and purchase intention (Shukla and Mishra, 2021). Zhou et al (2016) found the mediating effect of trust among source credibility, argument quality, and purchase intention.…”
Section: Trust and Purchase Intentionmentioning
confidence: 96%
“…Zarifah Dhabitah Mahat and Hafiz Hanafiah (2020) found a partial mediation effect of trust in the relationship between travelers' information adoption and behavioral intentions. Further, trust was found to mediate the relationship between review credibility and purchase intention (Shukla and Mishra, 2021). Zhou et al (2016) found the mediating effect of trust among source credibility, argument quality, and purchase intention.…”
Section: Trust and Purchase Intentionmentioning
confidence: 96%
“…Consumers receive information through information and communication technology either from fellow travelers or from marketers (Jalilvand et al, 2017; Shukla & Mishra, 2021). Consumers trust peer consumers more than they trust marketers (Litvin et al, 2008; Sen & Lerman, 2007; Verma & Dewani, 2020).…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%